To what extent can China's near-term air pollution control policy protect air quality and human health? A case study of the Pearl River Delta region. (8th October 2015) - Jiang, Xujia; Hong, Chaopeng; Zheng, Yixuan; Zheng, Bo; Guan, Dabo; Gouldson, Andy; Zhang, Qiang; He, Kebin
Abstract: Following a series of extreme air pollution events, the Chinese government released the Air Pollution Prevention and Control Action Plan in 2013 (China's State Council 2013). The Action Plan sets clear goals for key regions (i.e. cities above the prefecture level, Beijing-Tianjin-Hebei Province, the Yangtze River Delta and the Pearl River Delta) and establishes near-term control efforts for the next five years. However, the extent to which the Action Plan can direct local governments' activities on air pollution control remains unknown. Here we seek to evaluate the air quality improvement and associated health benefits achievable under the Action Plan in the Pearl River Delta (PRD) area from 2012 to 2017. Measure-by-measure quantification results show that the Action Plan would promise effective emissions reductions of 34% of SO2, 28% of NOx, 26% of PM2.5 (particulate matter less than 2.5 μ m in diameter), and 10% of VOCs (volatile organic compounds). These emissions abatements would lower the PM2.5 concentration by 17%, surpassing the 15% target established in the Action Plan, thereby avoiding more than 2900 deaths and 4300 hospital admissions annually. We expect the implementation of the Action Plan in the PRD would be productive; the anticipated impacts, however, fall short of the goal of protecting the health of local residents, as there are still more than 33 million people living in places where the annual mean ambient PM2.5 concentrations are greater than 35 μ g m −3, the interim target-3 of the World Health Organization (WHO). We therefore propose the next steps for air pollution control that are important not only for the PRD but also for all other regions of China as they develop and implement effective air pollution control policies.